Evolutionary biology: a new phylogenetic framework for an iconic plant radiation - Carruthers, T; Muñoz-Rodríguez, P; Scotland, RW (Cell Press, 2020)
Studies in island systems underpin much of our knowledge of macroevolution. A new study of the Galápagos giant daisies adds to this tradition. A time-calibrated phylogeny is presented that offers insights into the factors associated with diversification, providing a framework for further studies to investigate processes underlying these findings.